Mental Image and its Impact on Types of Errors in Mathematical Problem Solving: A Case Study - Munawwir, Zainul; Susanto, Susanto; Suwito, Abi (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
Students' difficulties in visualizing geometric objects often trigger various errors in problem-solving. Although mental imagery has an important function in clarifying the shape, position, and relationships between geometric elements, research specifically examining its relationship with student error types is still limited. This study aims to describe the relationship between mental imagery and student error types in solving geometric problems. The research method used is a qualitative approach with a case study design. The research subjects consisted of three mathematics education students selected based on the variety of errors they made. Data was collected through geometry tests, observations, think-alouds, and in-depth interviews. The results showed that inaccurate or incomplete mental imagery led to the emergence of visual representation errors, conceptual errors, procedural errors, and calculation errors. Mental imagery that is not integrated with conceptual and procedural understanding causes students to misinterpret problems. The contribution of this study emphasizes the importance of strengthening visualization skills and integrating geometric concepts in learning to minimize students' cognitive errors.